2012
DOI: 10.1111/imm.12020
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐interleukin‐33 inhibits cigarette smoke‐induced lung inflammation in mice

Abstract: SummaryThe mechanism by which cigarette smoke (CS) causes chronic obstructive pulmonary disease (COPD) is poorly understood. Interleukin-33 (IL-33) is a pleiotropic cytokine predominantly expressed in lung tissue and can elicit airway inflammation in naive mice. We tested the hypothesis that IL-33 is induced by CS and contributes to CS-mediated airway inflammation in a mouse model of CS-induced COPD. Groups of mice were exposed to CS three times per day for 4 consecutive days. The expression levels of IL-33 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 40 publications
(125 reference statements)
4
54
1
Order By: Relevance
“…A recent study using a mouse model showed that the expression levels of IL-33 and ST2 were markedly enhanced in the lung tissue after inhalation of cigarette smoke [61]. This observation supports those presented by Hacker et al [62], who reported increased serum levels of soluble ST-2 in COPD patients compared with healthy controls.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study using a mouse model showed that the expression levels of IL-33 and ST2 were markedly enhanced in the lung tissue after inhalation of cigarette smoke [61]. This observation supports those presented by Hacker et al [62], who reported increased serum levels of soluble ST-2 in COPD patients compared with healthy controls.…”
Section: Discussionsupporting
confidence: 82%
“…Intranasal anti-IL-33 antibody significantly inhibited cigarette smoke-induced lung inflammation in mice, as evidenced by reduced levels of IL-33 and ST2, as well as decreased number of neutrophil and macrophage infiltration along with decreased expression of inflammatory cytokines (IL-1b, TNF, IL-17) (Qiu et al, 2013). Mice challenged with ovalbumin and then treated with anti-IL-33 antibody or sST2 showed negative regulation of ovalbumin-induced allergic airway inflammation (Lee et al, 2014); both treatments decreased Th2 cytokine levels in bronchoalveolar lavage fluid and decreased the count of eosinophils (Lee et al, 2014).…”
Section: Treatment Possibilitiesmentioning
confidence: 94%
“…Inflammation mediated by tobacco smoking, which is associated with tongue SCC, induces the expression of IL-33/ST2 in mice [25]. In the present study, we determined the expression of IL-33 in patients with tongue SCC using immunohistochemistry and assessed the relationship between the expression of IL-33 and prognosis of tongue SCC.…”
Section: Introductionmentioning
confidence: 89%